Research on Aluminum Honeycomb Buffer Device for Soft Landing on the Lunar Surface - Wei Wei (Hindawi Limited, 2021)
To obtain the resources of the moon, humans have launched a series of exploration activities on the moon, and the landing buffer device is an indispensable device on the lander required to perform lunar surface exploration missions. It can effectively protect the lander during landing scientific payloads such as instruments on the lander. Based on the mechanical properties and deformation mechanism of the aluminum honeycomb as buffer material, this paper compares and analyzes different simulation schemes and finally establishes the bonding model of the honeycomb by using the discrete element method; the parameters of the honeycomb material are matched through compression experiments to verify the discrete element honeycomb simulation and the feasibility of the scheme and its parameters. To meet the buffering requirements of large landers, a spider web honeycomb structure is proposed, its modeling method is studied by using the discrete element secondary development program, and the model is compressed as a whole to verify the energy consumption characteristics of the spider web honeycomb structure. Aiming at the honeycomb buffer device during the landing process, the cobweb honeycomb buffer structure and its corresponding landing coupling model were established using the discrete element method, the landing process was simulated and analyzed, and the landing results were predicted to verify the feasibility of the device, providing a reference for the design of the lander and its buffer device.